Beneficial Effects of Table Grape Use on Serum Levels of Omega-3 Index and Liver Function: A Randomized Controlled Clinical Trial - Notarnicola, Maria; De Nunzio, Valentina; Lippolis, Tamara; Tutino, Valeria; Cisternino, Anna; Iacovazzi, Palma; Milella, Rosa; Gasparro, Marica; Negro, Roberto; Polignano, Maurizio; Caruso, Maria (Biomedicines, 2022)
This clinical trial was aimed to investigate the effects of fresh table grape intake on the serum levels of the Omega-3 index, defined as the sum of eicosapentaenoic acid (EPA) + docosahexaenoic acid (DHA) levels. Forty consecutive healthy subjects were randomly assigned to the control group, receiving only dietary recommendations, and the grape group receiving a daily dose of 5 g of fresh table grape per kg of body weight, for 21 days. Compared with baseline, the grape treatment produced no significant difference in the serum levels of glucose, liver transaminase, and triglycerides, with the exception of cholesterol value, which was significantly reduced in both control and grape group (180.5 ± 20.32 vs. 196.1 ± 30.0 and 181.4 ± 21.9 vs. 194.3 ± 37.5, respectively). After 4 weeks from the end of grape treatment, the analysis of single fatty acids showed a significant increase in oleic acid content (14.15 ± 1.8 vs. 12.85 ± 1.6, p < 0.05) and a significant induction of the Omega-3 index (8.23 ± 1.9 vs. 6.09 ± 1.2, p < 0.05), associated with increased serum levels of adiponectin (24.09 ± 1.08 vs. 8.8 ± 0.7, p < 0.001). In contrast, the expression of fibroblast growth factor 21 (FGF21), a molecule associated with metabolic syndrome and liver disease, was significantly reduced (37.9 ± 6.8 vs. 107.8 ± 10.1, p < 0.001). The data suggest that the intake of fresh grape improves the Omega-3 index in the serum and exerts beneficial effects on liver function through the overexpression of adiponectin and the reduction in FGF21 levels.